Infestation, damage, and population dynamics of Phyllocnistis citrella Stainton (Lepidoptera: Gracillaridae) in Bahia Concha, Santa Marta (Colombia) - Socarrás, Manuel; Suárez, Hernando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
An experiment was conducted in the field and under laboratory conditions, in the farm El Centro located in Bahia Concha near Tayrona Park, Santa Marta (Colombia) and The Laboratory of Entomology at the University of Magdalena, respectively, during the first semester of 2004 and the second semester of 2005. Over an eight month period, the damage percentage, infestation, and population fluctuation were determined, as well as observations made, of natural enemies of the citrus crop miner Phyllocnistis citrella (Lepidoptera: Gracillaridae) in three species of citrus: tangelo Minneola, mandarin Clementina and common acid lime sown in an area of 14 ha. The results revealed an average 30.95% damage with the highest damage in lime of 47% at the mid-point of tree height. In mandarin, the damage was 36% and 18% in tangelo at the mid-point of tree height. The main population peaks were highest in September in mandarin and in November in lime. A direct relation between precipitation and population dynamics was observed. In the laboratory the parasite Elasmuis sp. (Hymenoptera: Eulophidae) emerged and, in the field, the most important predators identified were the wasp Polybia occidentalis (Hymenoptera: Vespidae) and Chrysoperla sp. (Neuroptera: Chrysopidae). C. reticulate x C. paradise. C. reticulata and C. limon. Field studies have revealed that P. citrella caused damage of 47% in lemon, 36% in mandarin and 18% in tangelo. Populations of the pest insect were important in September in mandarin and in November in lemon. A direct relation between precipitation and population dynamic were observed, while in the laboratory the parasitoid: Elasmus sp. (Hymenoptera: Eulophidae) was identified, and in the field Polybia occidentalis (Hymenoptera: Vespidae), were found to be the most effective predator.